42.6k views
4 votes
Which value is equivalent to 48 ÷ ((2 + 6) × 2) − 1? A) -12 B) 2 C) 3 1 5 D) 3

User Dorad
by
6.3k points

2 Answers

5 votes

Final answer:

The value equivalent to 48 ÷ ((2 + 6) × 2) - 1 is B) 2.

Step-by-step explanation:

To solve this problem, we need to follow the order of operations (also known as PEMDAS or BODMAS).

First, we calculate the expression inside the parentheses: 2 + 6 = 8.

Next, we multiply the result by 2: 8 × 2 = 16.

Finally, we divide 48 by the result: 48 ÷ 16 = 3.

After that, we subtract 1: 3 - 1 = 2.

Therefore, the value equivalent to 48 ÷ ((2 + 6) × 2) - 1 is 2.

User JasonMortonNZ
by
6.6k points
1 vote

Answer:

B) 2

Step-by-step explanation:

Given expression,

48 ÷ ((2 + 6) × 2) − 1

In simplification we follows the following order,

B = Bracket

O = Of

D = Division

M = Multiplication

A = Addition,

S = Subtraction,

Thus, steps of solving the given expression by following BODMAS are as follow,


(48)/((2 + 6) * 2)-1


=(48)/(8* 2)-1


=(48)/(16)-1


=3-1


=2

Hence, OPTION B is correct.

User Everth
by
5.8k points